Faktor-Faktor yang Mempengaruhi Minat Berwirausaha pada Siswa SMK - Miftachul janah sarwono; Miftachul Janah Sarwono; Sri Handajani; Dwi Kristiastuti Suwardiah; Mauren Gita Miranti (Jurnal Sains Boga, 2022)
Abstract The objective of this study were to determine: (1) the influence of intrinsic factors partially on the entrepreneurship interest of XII class’s students majoring in culinary at SMK Negeri 3 Blitar; (2) the influence of extrinsic factors partially on the entrepreneurship interest of XII class’s students majoring in culinary at SMK Negeri 3 Blitar; (3) the influence of intrinsic and extrinsic factors simultaneously on the entrepreneurship interest of XII class’s students majoring in culinary at SMK Negeri 3 Blitar. This study was a survey using quantitative descriptive design. Data collection was conducted by distributing questionnaires. Data were analyzed by multiple linear regression analysis with the stages of classical assumption test analysis, namely: multicollinearity test, auto-correlation, heteroscedasticity and normality test and model feasibility test, namely: T test, F test and coefficient of determination. The result of this study showed that: (1) intrinsic factors partially influenced the entrepreneurship interest of XII class’s students majoring in culinary at SMK Negeri 3 Blitar; (2) extrinsic factors partially influenced the entrepreneurship interest of XII class’s students majoring in culinary at SMK Negeri 3 Blitar; (3) intrinsic and extrinsic factors simultaneously influenced the entrepreneurship interest of XII class’s students majoring in culinary at SMK Negeri 3 Blitar (96.2%). Keywords: entrepreneurship, culinary, adolescent, interest, education, family.